Development and evaluation of osmo-dried peel sticks from galgal (Bangladesh Journal of Botany, 2023)
The lab experiment on development and evaluation of osmo-dried peel sticks from galgal was laid out with six treatment combinations i.e. dipping concentration of sugar and jaggery solution of 30, 40 and 500Brix with three replications. The experiment was conducted by using factorial completely randomized design. The osmo-dried galgal peel sticks were analysed for chemical composition and sensory qualities at an interval of one month till three months of storage period at ambient conditions. However, with an advancement of storage period an increasing trend was observed in reducing sugar, total sugar and hunter colour a*value. However, a decreasing trend was observed in moisture, ash, hunter colour L*and b*value, and pectin content. The galgal peel sticks prepared with treatment T3(500Brix with sugar) showed statistically higher maximum value of colour, flavour, texture and taste during the three months of storage period and was more acceptable than other treatments.Bangladesh J. Bot. 52(1): 17-25, 2023 (March)